(untitled) (Bangladesh Journal of Zoology, 2025)
The mola carplet (Amblypharyngodon mola) is a well-adored small indigenous fish species (SIS) in Bangladesh. To evaluate the molecular and classical identification of the fungus associated with dried fish, the mola carplet was the subject of the current study. Aspergillus lentulus, a very common fungus in mola carplet was characterized molecularly using a 590 bp PCR product of its ITS (internal transcribed spacer) region. The molecular phylogenetic tree constructed therefrom showed 100% sequence similarity in A. lentulus species complex. The impact of cultural medium on mycelial growth and development of A. lentulus was pointed. The mycelial growth of A. lentulus was highest (71 mm) on the potato dextrose agar (PDA) medium, followed by (53 mm) in glucose peptone (GLP), (51 mm) in potato sucrose agar (PSA), (39 mm) in yeast extract agar (YEA), and (29 mm) Hoppkins (29 mm), respectively. A. lentulus grew and developed vegetatively best at 30°C and 7.0 pH, respectively. As far as we are aware, this experimental identification of the dry fish fungus Aspergillus lentulus from the mola carplet is the first report and confirmation of a fungus in Bangladesh using both traditional and molecular methods. Bangladesh J. Zool. 53(2): 209-218, 2025